2007
DOI: 10.1111/j.1439-0442.2007.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia Otitis Externa in the Dog: The Effect of Heat‐fixing Otic Exudate for Cytological Analysis

Abstract: This study was conducted on 32 dogs with Malassezia otitis externa to determine the effect of heat-fixing otic exudate on cytological analysis. Malassezia infection was confirmed by cytological examination of otic exudate. Otic discharge collected with cotton swabs was then rolled onto glass slides. One slide per dog was heat-fixed prior to staining; the other slide was not heat-fixed. The number of yeast in 10 oil-immersion fields (1000 x magnification) was counted for both slides from each dog. Heat-fixing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 4 publications
(17 reference statements)
0
7
0
6
Order By: Relevance
“…In previous studies, the otic debris or exudate was collected with only one cotton swab, which was then rolled on to two slides (Griffin and others 2007) or four slides (Toma and others 2006). The primary aim of the present study was to determine the reproducibility of sampling for otic cytology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the otic debris or exudate was collected with only one cotton swab, which was then rolled on to two slides (Griffin and others 2007) or four slides (Toma and others 2006). The primary aim of the present study was to determine the reproducibility of sampling for otic cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies evaluated the microbial isolates and susceptibility patterns of dogs with otitis externa (Cole and others 1998, Graham-Mize and Rosser 2004), while others compared staining methods (Toma and others 2006), correlated cytological findings with culture results (Cole and others 1998, Graham-Mize and Rosser 2004) and/or their antimicrobial susceptibility patterns from parallel cultures (Graham-Mize and Rosser 2004). Recently, it was demonstrated that heat fixing has no effect on cytological results if yeast organisms are involved (Griffin and others 2007). However, to the authors' knowledge, the reproducibility of sampling cytology specimens from the ear canal has not been evaluated.…”
mentioning
confidence: 99%
“…In der Regel wird hierfür ein trockener Watteträger ohne Sichtkontrolle ins Ohr eingeführt und zweibis dreimal rotiert, dann auf einem Objektträger abgerollt und das Präparat mittels DiffQuick ® oder Hemacolor ® gefärbt. Eine Hitzefixation bringt keine besseren Ergebnisse (3,38). Durch die zytologische Untersuchung lässt sich meist gut differenzieren, ob es sich um eine Malassezieninfektion, eine Infektion mit kokkoiden oder stäbchenförmigen Bakterien oder eine Mischinfektion handelt (55).…”
Section: Zytologische Und Mikrobiologische Untersuchungunclassified
“…For parasitological analysis of mange infections, microscopic examination of skin scrapings and ear wax samples at 40 × under a dissecting microscope and at 100 × and 400 × under an optical microscope was performed for the presence of mites and eggs, then digested in boiling 10% NaOH, centrifuged and microscopically examined (at 100 × and 400 ×) according to the method described by Sréter et al ( Sréter et al, 2003 ). Malassezia yeasts found in skin histological sections and in ear wax samples were identified by their morphology ( Griffin et al, 2007 , Outerbridge, 2006 ), while Otodectes and Sarcoptes mites were identified according to Sweatman ( Sweatman, 1958 ) and Fain ( Fain, 1968 ), respectively.…”
Section: Methodsmentioning
confidence: 99%